2019
DOI: 10.1002/uog.20208
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis has no additional value in fetal aberrant right subclavian artery: description of 268 pregnancies and systematic literature review

Abstract: Objectives Fetal aberrant right subclavian artery (ARSA) is a relatively common sonographic finding. Several studies have reported a significant association between ARSA and Down syndrome, as well as 22q11.2 microdeletion. The objective of this study was to assess the risk of abnormal chromosomal microarray analysis (CMA) findings in a large cohort of pregnancies with fetal ARSA as an isolated, as well as a non-isolated, sonographic anomaly. A secondary objective was to review the literature, examining the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…Isolated ARSA is frequently considered to be benign and not associated with T21 or 22q11.2 deletion [18]. Some scholars have even concluded that CMA had no additive value in such cases, but a detailed ultrasound scan should be performed to further evaluate the risk of genetic abnormalities [10,13]. But some scholars suggested that CMA should be considered in cases of prenatally diagnosed fetal cardiovascular malformations, even if the lesion is apparently isolated based on prenatal imaging [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated ARSA is frequently considered to be benign and not associated with T21 or 22q11.2 deletion [18]. Some scholars have even concluded that CMA had no additive value in such cases, but a detailed ultrasound scan should be performed to further evaluate the risk of genetic abnormalities [10,13]. But some scholars suggested that CMA should be considered in cases of prenatally diagnosed fetal cardiovascular malformations, even if the lesion is apparently isolated based on prenatal imaging [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely accepted for use in fetuses with AAA accompanied with cardiac anomalies or non-cardiac malformations, but its use in the management of cases with an isolated AAA remains controversial. For fetuses with ARSA as an isolated finding, an invasive procedure for CMA testing is not indicated, unless additional ultrasound abnormalities are detected [10,13]. Some authors have recommended karyotyping and FISH for chromosome 22q11.2 microdeletion screening in all fetuses with RAA [3,14].…”
Section: Data Interpretationmentioning
confidence: 99%
“…Absent thymus; in aCGH 22q11 deletion confirmation; Ao -aorta; PT -pulmonary trunk; SVC -superior vena cava increasing the risk by 10-fold [32]. However, the last study [33] showed that Down syndrome was present only in 0.4% of cases of isolated ARSA and authors concluded that isolated ARSA should be treated as a soft marker for Down syndrome.…”
Section: Abnormalities Detected In Color Doppler Modalitymentioning
confidence: 99%
“…Most studies indicated that isolated ARSA had no much clinical signi cance, and there was no need to serve an invasive prenatal chromosomal testing [8][9][10][11][12]. In Italy, an invasive procedure was offered to all patients with intermediate risk and a retrotracheal ARSA [10].…”
Section: Introductionmentioning
confidence: 99%